Controversies and Advances in Adult Intracranial Bypass Surgery in 2020. Issue 1 (7th September 2020) - Raper, Daniel M S; Rutledge, W Caleb; Winkler, Ethan A; Meisel, Karl; Callen, Andrew L; Cooke, Daniel L; Abla, Adib A
Abstract: Cerebral revascularization utilizing a variety of bypass techniques can provide either flow augmentation or flow replacement in the treatment of a range of intracranial pathologies, including moyamoya disease, intracranial atherosclerotic disease, and complex aneurysms that are not amenable to endovascular or simple surgical techniques. Though once routine, the publication of high-quality prospective evidence, along with the development of flow-diverting stents, has limited the indications for extracranial-to-intracranial (EC-IC) bypass. Nevertheless, advances in imaging, assessment of cerebral hemodynamics, and surgical technique have changed the risk-benefit calculus for EC-IC bypass. New variations of revascularization surgery involving multiple anastomoses, flow preserving solutions, IC-IC constructs, and posterior circulation bypasses have been pioneered for otherwise difficult to treat pathology including giant aneurysms, dolichoectasia, and medically refractory intracranial atherosclerosis. This review provides a practical update on recent advances in adult intracranial bypass surgery.